2020
DOI: 10.12703/b/9-16
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in tendinopathy

Abstract: endinopathy refers to the clinical diagnosis of activity-related pain resulting in a decline in tendon function. In the last few years, much has been published concerning the basic science and clinical investigation of tendinopathy and debates and discussions to new questions and points of view started many years ago. This advances review will discuss the current thinking on the basic science and clinical management of tendinopathy and in particular new findings in the tendon repair space that are relevant to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
(39 reference statements)
0
5
0
1
Order By: Relevance
“…Это сопровождается снижением прочности сухожилия и энтезиса, повышением механического стресса и более легкой индукцией локального воспаления. Кроме того, неоангиогенез и спраутинг (разрастание новообразованных нервных волокон) (5):88-93 определяют повышение периферической болевой чувствительности и способствуют развитию периферической гипералгезии [10][11][12][13].…”
Section: патогенез помтunclassified
“…Это сопровождается снижением прочности сухожилия и энтезиса, повышением механического стресса и более легкой индукцией локального воспаления. Кроме того, неоангиогенез и спраутинг (разрастание новообразованных нервных волокон) (5):88-93 определяют повышение периферической болевой чувствительности и способствуют развитию периферической гипералгезии [10][11][12][13].…”
Section: патогенез помтunclassified
“…Tendinopathy is histologically characterized by a failed healing response of hypercellularity, hypervascularity and rounding of tenocytes with loss of parallel cell arrangement [ [33] , [34] , [35] ]. The collagen type III/type I ratio and sulfated glycosaminoglycan production increase in tendinopathy.…”
Section: Common Inflammatory Mediators Linking Obesity and Tendinopathymentioning
confidence: 99%
“…Tendinopathy is previously considered as a degenerative disease with an absence of infiltration of inflammatory cells [ [36] , [37] , [38] ]. However, recent studies have reported signs of inflammation, including the presence of inflammatory cells or an increase in inflammatory markers in the pathological clinical samples [ 33 , 34 , [39] , [40] , [41] ]. The discrepancy is likely due to the sub-optimal method used for the detection of inflammatory cells in the earlier studies.…”
Section: Common Inflammatory Mediators Linking Obesity and Tendinopathymentioning
confidence: 99%
“…Tendinopathy is multifactorial pathology, that could lead to chronic pain and functional impairment [ 1 ]. The rotator cuff [ 2 ], the long head of the biceps [ 3 ], the wrist extensors and flexors [ 4 ], the adductors [ 5 ], the patellar tendon, the Achilles tendon [ 6 ] and the posterior tibial tendon [ 7 ] are the most affected tendons.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no treatments of choice for tendinopathies as no strong evidence has yet been found that one treatment is better than another [ 1 , 23 , 24 ]. Until a few years ago, eccentric exercise [ 25 , 26 , 27 ] and extracorporeal shock wave therapy (ESWT) [ 28 ] showed significant effects on both pain and functional recovery.…”
Section: Introductionmentioning
confidence: 99%